ChemInform Abstract: [Cu(NHC)]‐Catalyzed C—H Allylation and Alkenylation of Both Electron‐Deficient and Electron‐Rich (Hetero)arenes with Allyl Halides. Issue 23 (May 2016) - Xie, Weilong; Chang, Sukbok
Abstract: A new protocol for the C—H allylation of polyfluoroarenes is disclosed by using a [Cu(NHC)] catalyst.